Sensitive Amperometric Detection of Hydroxylamine at Electropolymerized Curcumin Film Coated Pencil Graphite Electrode - Gunes, Mehmet; Sap, Ayse; Karakaya, Serkan; Yaman, Mehmet; Dilgin, Yusuf (Wiley-V C H Verlag Gmbh, 2023)
In this study, a sensitive electrochemical method was developed for the determination of hydroxylamine (H-A) using a curcumin-modified pencil graphite electrode prepared with the electropolymerization of curcumin (PolyCurc-PGE). The PolyCurc-PGE showed a remarkable electrocatalytic response for H-A oxidation compared with bare PGE. Amperometric and cyclic voltammetric measurements were performed based on the electrocatalytic oxidation of H-A at PolyCurc-PGE. Some parameters, such as monomer concentration, pH, and cycle number during electropolymerization, were optimized to obtain the best electrochemical response of the modified electrode towards H-A. Results show that the PolyCurc-PGE gives a linear response towards H-A oxidation in the range from 0.50 mu M to 500 mu M (R-2=0.9984). In addition, the sensitivity and detection limit (LOD) of PolyCurc-PGE were found to be 5432 mu A mM(-1) cm(2) and 0.15 mu M H-A, respectively. The developed amperometric method was successfully applied to determine H-A in pharmaceutical and water samples, and acceptable results were obtained with high accuracy and precision.
Keywords: amperometry; electrochemistry; electropolymerization; hydroxylamine; sensors